Sistem Informasi Penjualan Berbasis Web Dengan Metode Prototype - Alfitri Rizka Rinanda; Okvrillia Reony Ondri; Sulistiyono (CV. Shofanah Media Berkah, 2023)
Restaurant sales are an important element in the food and beverage industry. To improve operational efficiency and provide a superior customer experience, the application of a web-based restaurant sales information system is a relevant solution. In this journal, we discuss the development and implementation of a web-based Restaurant Sales Information System that aims to increase operational efficiency and is specifically designed for Bakut Mumu restaurants and includes various features that assist in managing sales and daily operations. In this case, the web-based Bakut Mumu restaurant sales information system also provides benefits in terms of sales data analysis. Collected sales data can be analyzed to gain insight into sales and performance of menus or promotions. With this information, restaurants can make better strategic decisions in menu development, service improvement and marketing strategy.